The Creation of a Select Image of the World: A Look at the Reflection of the 1889 Paris World’s Fair - Zurbano Zuazu, Irati; Vergara Iracheta, Alba (Huarte de San Juan. Geografía e Historia, 2025)
The Universal Exhibitions of the 19th century can be analysed as generators of collective imaginaries about nature, through the creation of a select image of the world. From socio-environmental history, cultural history and the history of mentalities, as well as through the quantitative and qualitative analysis of the iconographic representations of the Official Bulletin of the Paris Universal Exhibition of 1889, we have studied the idea of progress, shaped by the environment and otherness. This interpretative analysis of the images has been made possible by the iconographic heritage generated by the exhibition, where, by combining different perspectives, we have analysed the construction of images and the hierarchies present within them. In the environmental case, we studied how the illustrations reflected the understanding of nature as a resource at man’s service. They also illustrated and exalted the conquest of space and technical progress. At the same time, the construction of the different othernesses reflected in the engravings of the bulletin has also been analysed from a social point of view. In both cases, there is a clear representation of the foreign as something conquerable, exotifying elements external to the Western world.
Keywords: collective imagination; otherness; socio-environmental; heritage; nature